POTENSI HUTAN RAWA GAMBUT SEBAGAI SILVOFISHERY - Rosanti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2014)
This paper reports the results of the study on the peat swamp in the Kedaton Village as Silvofishery. Research was conducted between May till October 2012. This research was carried out using survey method. Sample was taken by purpossive sampling. Data and information gathered included diversity index of vegetation, selected soil and water quality, plankton, macrozoobenthos, water insect and fish. Results of the study get 2 species of vegetation in tree, 4 genera of plankton, 3 genera of macrozoobenthos, 2 species of insect water and 3 species of fish. That peat swamp in the Kedaton Village have potency as Silvofishery, although diversity index of vegetation and plankton was median chategory, and diversity index of macrozoobenthos, insect water and fish was low chategory.Key words : peat swamp, vegetation, plankton, macrozoobenthos, fish